Study of water droplet impinging on surface - Yap, De Cai (Nanyang Technological University, 2021)
This report presents experimental investigations and analysis of water droplet impingement through observation of the transient process of water droplet impinging on a moving solid aluminium surface by using a high-speed camera. There are many applications for water droplet impingement, some of them are spray cooling of turbine blades, electronic devices, and internal combustion engines. One benefit of water droplet impingement is that it can be used for improving the heat transfer rate on the application’s surfaces. The transient process of the water droplet happens very fast as it travels from its source start point to the impinged target surface destination. All the changes and phenomenon that occurs during this course of action would not be able to be precisely captured in detail by the human naked eye. A high-speed camera is thus used for capturing all these transient processes of the water droplet impingement. The high-speed camera allows for capturing up to a million frames per second (FPS) and produce very high-resolution images and videos. With such capabilities of capturing huge number of FPS, all the occurrences in the transient process of the water droplet impingement can be well captured in detail, in the form of a video. In this study, the two governing parameters are the droplet release height and varying surface velocities. The detailed experimental procedures are documented and the characteristics of the water droplets impinging onto the moving surface have been captured, including the maximum spreading diameters at various impinging speeds. It is found that different droplet release height and different surface speeds affects and produces different results for droplet impingement; such as the droplet spreading factor.